2017
DOI: 10.2147/jpr.s143869
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and epigenetic epidemiology of chronic widespread pain

Abstract: The etiology underlying chronic widespread pain (CWP) remains largely unknown. An integrative biopsychosocial model seems to yield the most promising explanations for the pathogenesis of the condition, with genetic factors also contributing to disease development and maintenance. Here, we conducted a search of studies investigating the genetic and epigenetic epidemiology of CWP through electronic databases including Web of Science, Medline, PubMed, EMBASE, and Google Scholar. Combinations of keywords including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 52 publications
(79 reference statements)
1
29
0
Order By: Relevance
“…The findings in the current study are in agreement with existing literature showing that parental chronic musculoskeletal pain has a strong influence on the development of chronic musculoskeletal pain in offspring (Lier et al., ) and support the findings of twin studies demonstrating a high heritability of CWP (Kerr and Burri, ). Numerous studies have identified specific genes (or single nucleotide polymorphisms) responsible for chronic painful conditions (Livshits et al., ; Ferreira et al., ; Hocking et al., ), including fibromyalgia (Arnold et al., ; Buskila et al., ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The findings in the current study are in agreement with existing literature showing that parental chronic musculoskeletal pain has a strong influence on the development of chronic musculoskeletal pain in offspring (Lier et al., ) and support the findings of twin studies demonstrating a high heritability of CWP (Kerr and Burri, ). Numerous studies have identified specific genes (or single nucleotide polymorphisms) responsible for chronic painful conditions (Livshits et al., ; Ferreira et al., ; Hocking et al., ), including fibromyalgia (Arnold et al., ; Buskila et al., ).…”
Section: Discussionsupporting
confidence: 93%
“…The influence shared familial factors (including genetics and shared environmental factors) have on the development of CWP, and lifestyle behaviours need to be considered when interpreting our results. The heritability of CWP (Kerr and Burri, ), obesity (Herrera and Lindgren, ) and physical activity engagement is high (de Vilhena e Santos et al., ), and numerous twin studies have shown that the association between lifestyle behaviours and chronic conditions (such as low back pain) disappear once genetics and shared environmental factors have been controlled for (Dario et al., ; Zadro et al., ). Therefore, the possibility of shared familial factors confounding the effects of BMI on the parent–offspring transmission of CWP cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…Pain is an important biological warning signal that can be triggered by stress and a multitude of other factors. There is a genetic and epigenetic variation of pain sensitivity as for all types of interoceptive signal. Hunger and pain to well‐being and pleasure vary with the genetic set‐up and epigenetic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Biological, biomechanical, environmental, psychological, and social factors have been associated with the onset and perpetuation of chronic MSK. 30,52,77 Psychological factors are probably the most influential factors in the perception, processing, interpretation, and coping with chronic pain. 94,124 Fear is one of the psychological factors that has received extra empirical attention in the last 2 decades.…”
mentioning
confidence: 99%